A K‐band fully differential 4‐channel transmitter IC in 65 nm CMOS technology. Issue 11 (21st May 2020) - Park, Jeongsoo; Kim, Jinhyun; Kim, Jeong‐Geun
Abstract: A K‐band 4‐channel transmitter IC with fully differential architecture is presented in this paper for beamforming phased‐array system. This IC uses commercial 65 nm CMOS technology. The major building blocks of this IC are 3‐stage medium power amplifiers (MPAs) with resistive feedback network to control the gain, 6‐bit phase shifter with tuning bit, 15 dB attenuators, 4‐way power divider consisting switches, and a Marchand balun. All above components are designed by differential architecture. The cross‐connected switch type 180° phase shifter and the differential 4‐way power divider is implemented for low insertion loss and small chip size compared with its conventional switched type phase shifter and three differential 2‐way power dividers, respectively. This TX IC has −5 dB overall gain at 21‐23 GHz. Furthermore, it also available phase shifting of 360° with 5.6° step and attenuating of 29 dB with 1 dB step at 21‐23 GHz, respectively. The RMS phase errors and the RMS amplitude error are achieved <3° and <1 dB at 21‐23 GHz, respectively. The achieved P 1dB and saturation power ( P SAT ) of this TX IC are >0 dB m and >6 dB m, respectively. The 4‐channel TX IC consumes 140 mA of DC current at 2.5 V supply voltage. The overall dimension of 4‐channel TX IC is 3 × 1 mm 2 .